The Effect Of Using Small Group Discussion On The Second Grade Students’ Speaking Skill - Suryadi, Hendra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
Speaking is one of the main purposes of language learning in that it is an ability to transfer some ideas to other people clearly and correctly. In other words, he or she can communicate his or her ideas well to other people. As speaking dominates all activities in the English subject, the language components, namely pronunciation, fluency and vocabulary should also be learnt to support the language skills.  Based on the English teacher interview result that small group discussion have never been used by the teachers, speaking skill on the eighth grade students of junior high school of SMP Darul Muhajirin, so it was necessary to conduct a research in this school. The research design was quasi experimental. It began from conducting homogeneity test, deciding the experimental class and the control class, giving activities to the control class using the common technique and material usually applied by the English teacher and treatments to the experimental class that was using small group discussion in teaching speaking, then giving the same post-test to both classes, and the last analyzing the results of the post-test by using t-test. The result of this research The analysis of the post test results showed that there was a significant effect of using small group discussion that of speaking skill the experimental class got higher mean score than the control class (65, 1>57, 5) of the students’ speaking skill. Then, the result of data analysis using SPSS showed that the t-test value (2-tailed) 0.000, was less than 0.05.is expected to provide useful information for the English teacher to use interesting materials, that is, small group discussion in the English teaching learning process, especially in teaching speaking, since the small group discussion have never been used at SMPN Darul Muhajirin.